Factors affecting health-related quality of life in Thai children with thalassemia - Thavorncharoensap, Montarat (BioMed Central, 2010)
BACKGROUND: Knowledge of the factors associated with health-related quality of life (HRQOL) among patients with thalassemia is essential in developing more suitable clinical, counseling, and social support programs to improve treatment outcomes of these patients. In light of the limited research in this area, this study aims to examine factors associated with HRQOL among children and adolescents with thalassemia in Thailand. METHODS: A cross-sectional survey was conducted in three selected hospitals in Thailand during June to November 2006. PedsQL™ 4.0 Generic Core Scale (Thai version) was used to assess HRQOL in 315 thalassemia patients between 5 and 18 years of age. Other related clinical characteristics of the patients were collected via medical record review. RESULTS: The mean (SD) of the total summary score was 76.67 (11.40), while the means (SD) for the Physical Health Summary score and Psychosocial Health Summary score were 78.24 (14.77) and 75.54 (12.76), respectively. The school functioning subscale scored the lowest, with a mean of 67.89 (SD = 15.92). The following factors significantly affected the HRQOL of the patients: age; age at onset of anemia and age at first transfusion; pre-transfusion hemoglobin (Hb) level; receiving a blood transfusion during the previous three months; and disease severity. In addition, iron chelation therapy had a significant negative effect on HRQOL in the school functioning subscale. In contrast, serum ferritin level, frequency of blood transfusions per year, and gender were not significantly related to HRQOL among these patients. The results from multivariate analysis also confirmed these findings. CONCLUSIONS: To improve HRQOL of thalassemia patients, suitable programs aimed at providing psychosocial support and a link between the patient, school officials, the family and the physician are important, especially in terms of improving the school functioning score. The findings also confirmed the importance of maintaining a pre-transfusion Hb level of at least 9-10.5 g/dL. In addition, special care and attention should be given to patients with a severe condition, and those who are receiving subcutaneous iron chelation therapy.